Kaplan-meier-based survival analysis of Cylas formicarius following exposure to stored Metarhizium anisopliae formulations - Nina Lapinangga; Jacqualine Arriani Bunga; Jemrifs Herkanus Hati Sonbai; Yosefus Frederikus da-Lopez (Universitas Lampung, 2026)
The sweet potato weevil (Cylas formicarius) is a major pest of sweet potato crops, particularly in tropical regions. The entomopathogenic fungus Metarhizium anisopliae is a promising biological control agent; however, its application is often constrained by reduced viability during storage. This study evaluated the efficacy of a dry powder formulation of M. anisopliae stored under ambient tropical conditions for 1 to 6 months. Bioassays assessed conidial density, adult mortality, lethal time to kill 50% of the population (LT₅₀), and survival probability using Kaplan–Meier analysis. Formulations stored for up to 3 months maintained high efficacy, with mortality rates exceeding 82.9%, conidial densities above 2.5 × 10⁸ conidia/g, and LT₅₀ values below 120 hours. In contrast, storage beyond three months significantly reduced conidial viability, increased LT₅₀, and decreased mortality. Kaplan–Meier survival curves showed a clear decline in virulence with increasing storage duration, with the 6-month formulation exhibiting the slowest mortality progression. Significant differences in survival probabilities among storage durations were confirmed statistically (p < 0.05). Morphological observations confirmed fungal-induced mortality, characterized by cuticle darkening, tissue softening, mummification, and external sporulation. Conidial deterioration over time was likely associated with physiological factors such as oxidative stress, lipid peroxidation, and depletion of protective compounds including trehalose and mannitol. Overall, storage duration critically affected the bioefficacy of M. anisopliae. It is therefore recommended that dry formulations be used within three months of production to ensure optimal pest control. These findings provide practical guidance for improving fungal biopesticide shelf life in tropical integrated pest management programs.